Characteristics of Scratching Behavior Induced by Some Chemical Mediators in Hairless Mice - Miho Takubo; Yuhki Ueda; Rie Yatsuzuka; Shuishi Jiang; Yoko Fujii; Chiaki Kamei (Elsevier, 2006)
Abstract.: To find the characteristics of scratching behavior in hairless mice (HR-1), compound 48/80 and some putative chemical mediators of allergic reaction were injected intradermally into the backs of mice, and the number of scratching behaviors was measured. As reference mice, NC/Nga, ICR, and ddY mice were used. Scratching behavior in HR-1 and ICR mice was increased dose-dependently by compound 48/80. The same result was also observed with NC/Nga and ddY mice. However, the response in NC/Nga and ddY mice was far less than those of HR-1 and ICR mice. Similar to NC/Nga and ddY mice, HR-1 mice showed less sensitivity to histamine than ICR mice. On the other hand, the HR-1 mice showed a high response to serotonin compared with those of the NC/Nga and ddY mice. The scratching behavior in HR-1 mice induced by substance P was increased, but the effect was less potent than those in NC/Nga, ICR, and ddY mice. These results suggest that the scratching behavior induced by compound 48/80 in HR-1 mice is mainly attributable to serotonin. Keywords:: scratching behavior, compound 48/80, serotonin, histamine, HR-1 mice